(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Industrial wastewater refers to the contaminated water generated as a byproduct of industrial processes and activities. It encompasses a wide range of pollutants and contaminants, including chemicals, heavy metals, organic compounds, pathogens, and other harmful substances. Unlike domestic wastewater, which primarily originates from households and municipal facilities, industrial wastewater originates from various industrial sectors such as manufacturing, mining, chemical production, food processing, and power generation.